2018
DOI: 10.1016/j.antiviral.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Novel activities of safe-in-human broad-spectrum antiviral agents

Abstract: According to the WHO, there is an urgent need for better control of viral diseases. Re-positioning existing safe-in-human antiviral agents from one viral disease to another could play a pivotal role in this process. Here, we reviewed all approved, investigational and experimental antiviral agents, which are safe in man, and identified 59 compounds that target at least three viral diseases. We tested 55 of these compounds against eight different RNA and DNA viruses. We found novel activities for dalbavancin aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 65 publications
1
75
0
Order By: Relevance
“…Among the major players are purine analogues (including the commonly used cladribine, approved in 1992; fludarabine, approved in 1991; secondgeneration clofarabine, approved in 2004; and nelarabine, approved in 2005) and pyrimidine analogues (first approved in cytarabine in 1969, gemcitabine in 1996, azacytidine in 2004, decitabine in 2006, and floxuridine in 1970), which have had important roles in several cancer treatments (Parker, 2009). Some of the cytotoxic nucleoside analogues have recently proven their broad-spectrum antiviral activity towards life-threatening viruses (Ianevski et al, 2018. Among them, the cytidine analogue gemcitabine was reported to be 6th on the list of broad-spectrum antivirals that show in vitro activities .…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
See 2 more Smart Citations
“…Among the major players are purine analogues (including the commonly used cladribine, approved in 1992; fludarabine, approved in 1991; secondgeneration clofarabine, approved in 2004; and nelarabine, approved in 2005) and pyrimidine analogues (first approved in cytarabine in 1969, gemcitabine in 1996, azacytidine in 2004, decitabine in 2006, and floxuridine in 1970), which have had important roles in several cancer treatments (Parker, 2009). Some of the cytotoxic nucleoside analogues have recently proven their broad-spectrum antiviral activity towards life-threatening viruses (Ianevski et al, 2018. Among them, the cytidine analogue gemcitabine was reported to be 6th on the list of broad-spectrum antivirals that show in vitro activities .…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
“…Experimental studies have shown that azacitidine is a potent, broadspectrum antiviral agent. The range of viruses against which it shows activity includes AdV (Alexeeva et al, 2001(Alexeeva et al, , 2015, human metapneumovirus (HMPV) (Bösl et al, 2019), HIV-1 (Dapp et al, 2009;Rawson et al, 2016a), HIV-2 (Beach et al, 2014), Rift Valley fever virus (RVFV) (Ianevski et al, 2018, human T-lymphotropic virus (HTLV-1) (Diamantopoulos et al, 2012), HSV-1, and FLUAV (Ianevski et al, 2018). A study of azacytidine activity against HIV-1 and HIV-2 revealed that it primarily targets reverse transcription (in the form of 5azacytidine-triphosphate or 5-aza-2′-deoxycytidine triphosphate).…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
See 1 more Smart Citation
“…To get an estimate of the druggability of the hvPPI, we obtained known drug-gene interactions from DGIdb (Cotto et al 2018). The data from DGIdb included drug-gene interactions for 48 drugs that were investigational/experimental/approved safe-in-human antivirals compounds (Ianevski et al 2018). Among these 48 broad-spectrum-antivirals, 28 of them had targets that are part of the hvPPI.…”
Section: Combining Host-virus and Drug-gene Interactions Reveals Novementioning
confidence: 99%
“…Meta-analyses of such high-dimensional datasets have been crucial for identifying novel host factors as drug targets such as UBR4 in IAV infection (Tripathi et al 2015). Moreover, some of these factors represent drug targets for multiple viruses (Ianevski et al 2018).…”
Section: Introductionmentioning
confidence: 99%